2021
DOI: 10.1002/adfm.202109218
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment Engineering of Ru Single‐Atom Catalysts by Regulating the Cation Vacancies in NiFe‐Layered Double Hydroxides

Abstract: Single‐atom catalysts (SACs) with rationally designed microenvironments (defined as coordination environments and electronic configurations) show superior catalytic activity, selectivity, and stability in a majority of reactions. However, the construction of isolated SACs with definite microenvironments to understand the microenvironment–activity relationship is still challenging. Herein, a facile strategy is developed to construct a series of Ru SACs with tunable geometric and electronic structures by employi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 51 publications
3
32
0
Order By: Relevance
“…This one‐step route is more facile than the reported etching or anion exchange method. [ 9b,10b,14 ] For comparison, NiFe hydroxides with Fe vacancies prepared by oxygen oxidation for different durations were denoted as v Fe ‐Ni 2 Fe 1 ‐T ( T represents the oxidization time). The transmission electron microscope (TEM) image of Pt‐Ni 2 Fe 1 ‐24 in Figure a indicates the two‐dimensional structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This one‐step route is more facile than the reported etching or anion exchange method. [ 9b,10b,14 ] For comparison, NiFe hydroxides with Fe vacancies prepared by oxygen oxidation for different durations were denoted as v Fe ‐Ni 2 Fe 1 ‐T ( T represents the oxidization time). The transmission electron microscope (TEM) image of Pt‐Ni 2 Fe 1 ‐24 in Figure a indicates the two‐dimensional structure.…”
Section: Resultsmentioning
confidence: 99%
“…[ 13 ] For example, alkali etching amphiprotic metals (such as Zn and Al) could generate cationic vacancies, and single metal atoms could be anchored or electrodeposited at the cationic vacancies in the surface of LDH. [ 10b,14 ] In addition, Wang and coworkers developed an anion exchange method to introduce PtCl 6 2− to the interlaminar Fe 3+ of Ni 3 Fe LDH due to electrostatic attraction, and Pt single atoms were intercalated in the interlayer spacing through a subsequent electrochemical reduction. [ 9d ] Whereas, it is still highly desired to develop a facile method to prepare cationic vacancies selectively and load single metal atoms in the substrate from the application perspective.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure S6a, Supporting Information, high‐resolution XPS spectra of the Ru 3p signal exhibited two peaks at 463.7 eV (Ru 3p 3/2 ) and 485.9 eV (Ru 3p 1/2 ), which were assigned to Ru δ+ , revealing that the Ru SAs was stabilized by the MoSe 2 substrate and did not aggregate into nanoclusters. [ 50 ] SEM and TEM images showed that the morphology of the NWs was well maintained after the CP test (Figure S6b,c, Supporting Information). In addition, no apparent Ru NPs were detected based on the HRTEM image (Figure S6d, Supporting Information), and the corresponding HAADF‐STEM and elemental mapping illustrated that Ru, Mo, and Se were distributed uniformly on the surface of the MoSe 2 NSs (Figure S6e–h, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…However, CDT generally suffers from low chemical reaction rate, which restricts the further development of CDT. LDH-based singleatom catalysts possess ultra-high catalytic efficiency, 480,481 which is promising to conquer the mentioned obstacle of CDT. Thirdly, the construction of LDH-based theranostic platform can also facilitate real-time monitoring of the treatment process and effect to fulfill the practical application requirement.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%